DEVELOPMENT AND EVALUATION OF NOVEL ESTIMATION TECHNIQUES FOR IN VITRO DISSOLUTION STUDY AND VALIDATION PROTOCOL FOR ESCITALOPRAM AS ANTIDEPRESSANT DRUG AND THEIR FORMULATION - BAIRAGI, SHRIRAM H.; GHOSH, R. S. (International Journal of Pharmacy and Pharmaceutical Sciences, 2020)
Objective: To develop and validate the RP-HPLC method and in vitro dissolution study for escitalopram as antidepressant drug and their formulation. Methods: The chromatographic separation was done by using a C-18, 150 mm column and a mobile phase consisting of phosphate buffer (40%) and acetonitrile HPLC grade (60%). Detection was carried out at 211 nm with a flow rate of 1 ml/min with an injection of 20 μl. The method was validated with different parameters such as linearity, precision, accuracy, robustness, and limit of detection (LOD), the limit of quantification (LOQ) according to ICH guidelines. Results: The linear calibration curve was obtained in the concentration range of 0-50 μg/ml and gave an average correlation factor 0.992. The retention time was observed at 2.96 min. The Minimum concentration level at which the analyte can be reliably detected (LOD) and quantified (LOQ) were found to be 0.03 and 0.09 µg/ml, respectively. The relative standard deviation of intra and the inter-day assay was found to be less than 2. The dissolution studies show moderate dissolution (23.4%) after 45 min, but it reaches a plateau after approximately 25 min. Conclusion: This method was found to be simple, rapid and economic with less run time. The validated parameters manifest the method is reliable, linear, accurate and precise as well as robust with minor variations in chromatographic parameters. Therefore, the developed method can be applied for both routine analysis and quality control assay and it could be a very powerful tool to investigate the stability of escitalopram.